Methionine to cystine ratio in the total sulfur amino acid requirements and sulfur amino acid metabolism using labelled amino acid approach for broilers - Pacheco, Letícia G. [UNESP]; Sakomura, Nilva K. [UNESP]; Suzuki, Rafael M. [UNESP]; Dorigam, Juliano C. P.; Viana, Gabriel S. [UNESP]; Van Milgen, Jaap; Denadai, Juliana C. [UNESP] (Springer Nature, 2018)
Background: Assuming that part of Methionine (Met) is converted into Cystine (Cys), but ignoring the rates with which such phenomenon occurs may lead to an excessive supply of Met in poultry diets. Such inconvenient could be easily avoided with the knowledge of the ideal Met:Cys/Total sulfur amino acids (TSAA) ratio and the rates of Met conversion into Cys. Results: Met sources did not affect performance. Met:Cys/TSAA ideal ratio was determined using curvilinear-plateau regression model. Both optimum body weight gain and feed conversion ratio were estimated in 1007 g/day and 1.49, respectively, at 52% Met/TSAA ratio. Feed intake was not affected by Met:Cys/TSAA ratios. In the labelled amino acid assay, the rates with which Met was converted into Cys ranged from 27 to 43% in response to changes in Met:Cys/TSAA ratios, being higher at 56:44. Conclusion: Based on performance outcomes, the minimum concentration of Met relative to Cys in diets for broilers from 14 to 28 d of age based on a TSAA basis, is 52% (52:48 Met:Cys/TSAA). The outcomes from labelled amino acid assay indicate that highest the Met supply in diets, the highest is its conversion into Cys.
Keywords: Cystine; Methionine conversion; Methionine cycle; Stable isotopes; Sulfur amino acids